(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The objective of the current research is to identify the level of psychological resilience among postgraduate students at Tishreen University, and to identify the differences in the level of psychological resilience within four domains (clairvoyance-creativity-forming relationships-balance) according to the difference in both gender and specialization (medicine-education). The research sample consisted of (148) male and female students in the Faculty of Applied Medicine and the Faculty of Theoretical Education at Tishreen University during the first semester of the year (2021/2022). In order to achieve the objectives of the research, the researcher built a scale of (23) statements to measure psychological resilience in its four areas, after verifying its validity and reliability The appropriate barometric statistical methods were used - after verifying the moderation of the distribution - represented by the arithmetic mean, the standard deviation, the "T"test for two independent groups, and the Mann-Whitney test. The results showed the following: - A high level of psychological flexibility in the domains: (clairvoyance - forming relationships - creativity) among postgraduate students, except for the field of "balance", which was available in a medium degree There is no statistically significant difference among the research sample individuals in the two fields of psychological resilience (formation of relationships - creativity) according to the variable of specialization, while a statistically significant difference was found in the "clairvoyance" domain in favor of the students of the Faculty of Medicine, and a statistically significant difference was found in the "balance" domain in favor of College of Education students- There are no statistically significant differences in the level of psychological resilience among the research sample members due to the gender variable.